PENGARUH GUIDED DISCOVERY LEARNING TERHADAP MINAT DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS IV SDN 100311 PALSABOLAS - Harahap, Safri; Malinda, Leni (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2024)
This study aims to determine the effectiveness of the Guided Discovery Learning method in enhancing the interest and problem-solving abilities in mathematics of fourth-grade students at SDN 100311 Palsabolas. This research uses a quasi-experimental design with a nonequivalent control group design. The sample consists of all fourth-grade students at SDN 100311 Palsabolas, totaling 72 students. Data collection was conducted through interviews, observations, documentation, tests, and questionnaires. The results show that students' interest in learning and their problem-solving abilities in mathematics are higher when using the Guided Discovery Learning method compared to conventional methods. Hypothesis testing shows significant differences between the experimental and control groups. Thus, the Guided Discovery Learning method is effective in increasing students' interest and problem-solving abilities in mathematics.